ENHANCING ELT WITH TECHNOLOGY: A STUDY ON THE APPLICATION OF LEARNING THEORIES - Nisrina Dini Kholis; Sri Wahyuningsih; Tessa Widyaningtias Sagala (Universitas Pamulang, 2023)
In this era, many people worldwide have started using technology daily because it saves time and effort. This research investigates the application of learning theories in SMA Adiguna Bandar Lampung and how they are utilized in English language learning through technology. The descriptive qualitative method is employed in this study. To collect data, the researchers interviewed four SMA Adiguna Bandar Lampung teachers. Thematic data analysis was used to analyze the research findings. The results indicate the presence of behaviourism and cognitivism learning theories in SMA Adiguna Bandar Lampung; however, they are not integrated with technology. The researchers recommend further research with a broader scope and more participants. Therefore, educators can design effective instruction that supports learners in achieving their learning goals by applying appropriate learning theories.